TINJAUAN MOTIVASI MASYARAKAT DALAM MENGIKUTI SENAM LANSIA DI KELURAHAN PETANANG ILIR KECAMATAN LUBUKLINGGAU UTARA 1 - Nur Aida; Muhammad Supriyadi; Erick Salman ($$8@@&&$%K, 2021)
The purpose of this study was to determine how much influence the community's motivation in participating in elderly gymnastics in Petanang Ilir Village, Lubuklinggau Utara District 1. This research is a quantitative descriptive study using a survey method. The research subjects used were members of the elderly gymnastics group who participated in elderly gymnastics in Petanang Ilir Village totaling 11 people. The instrument used in the form of a questionnaire to analyze the data used quantitative descriptive statistics with percentages. The results showed the motivation of the elderly in participating in elderly gymnastics in Petanang Ilir Village was in the very high category with a frequency of 27,27% followed by the high category of 72,73%, the low category was at the frequency of 0% and very low at 0%. So it can be concluded that the motivation of the elderly in participating in elderly gymnastics in Petanang Ilir Village is mostly in the High category.